2021
DOI: 10.1158/2159-8290.cd-20-0873
|View full text |Cite|
|
Sign up to set email alerts
|

Durable Suppression of Acquired MEK Inhibitor Resistance in Cancer by Sequestering MEK from ERK and Promoting Antitumor T-cell Immunity

Abstract: MAPK targeting in cancer often fails due to MAPK reactivation. MEK inhibitor (MEKi) monotherapy provides limited clinical benefits but may serve as a foundation for combination therapies. Here, we showed that combining a type II RAF inhibitor (RAFi) with an allosteric MEKi durably prevents and overcomes acquired resistance among cancers with KRAS, NRAS, NF1, BRAFnon-V600, and BRAFV600 mutations. Tumor cell–intrinsically, type II RAFi plus MEKi sequester MEK in RAF complexes, reduce MEK/MEK dimerization, and un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 60 publications
1
54
0
2
Order By: Relevance
“…We conducted this screen in UM-Chor1, which is a clival chordoma cell line that has been proven to be sensitive to EGFR i s [9][10][11]. The analysis of whole genome sequencing data revealed that this cell line carries a PTEN L139* nonsense mutation [12], which has also been described in conventional glioblastoma, endometrial and breast cancers [30]. Tarpey et al did not detect any recurrent genetic drivers in their genetic analyses of 104 sporadic chordomas, but alterations in phosphoinositide-3 kinase signalling (including occasional mutations in PIK3CA and PTEN) were amongst the more common genetic events reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted this screen in UM-Chor1, which is a clival chordoma cell line that has been proven to be sensitive to EGFR i s [9][10][11]. The analysis of whole genome sequencing data revealed that this cell line carries a PTEN L139* nonsense mutation [12], which has also been described in conventional glioblastoma, endometrial and breast cancers [30]. Tarpey et al did not detect any recurrent genetic drivers in their genetic analyses of 104 sporadic chordomas, but alterations in phosphoinositide-3 kinase signalling (including occasional mutations in PIK3CA and PTEN) were amongst the more common genetic events reported [12].…”
Section: Discussionmentioning
confidence: 99%
“…Trametinib dose level for each tumor model was chosen based on the minimal dose required to elicit tumor stabilization or regression early on-treatment and near complete p-ERK suppression on d3 (Figure S2A). We used six murine syngeneic tumor models: (1) Braf V600E melanoma with high mutational burden (HMB) (YUMM1.7ER; Figure 2B) (Wang et al, 2017), (2) Nras Q61R melanoma (NIL; Figure 2C) (Hong et al, 2018), (3) Nras Q61R melanoma with high mutational burden (NILER1-4; Figure 2D) (Hong et al, 2021), (4) Nf1 À/À melanoma (mSK-Mel254; Figure 2E), (5) Kras G12C colorectal carcinoma (CT26; Figure 2F), and (6) Kras G12C pancreatic adenocarcinoma (KPC; Figure 2G).…”
Section: Previous Ict Enhances Mapki Responses In Melanoma Patientsmentioning
confidence: 99%
“…This sequential-combinatorial fusion may avoid the development of cross-resistance, raise the threshold for resistance evolution by stacking multiple therapeutic mechanisms of action, and permit one mode of therapy to prime responsiveness to the other, thereby creating synergy. Importantly, previous studies have implicated a role of antitumor immunity in prolonging, clinically and preclinically, the durability of MAPKi responses (Hong et al, 2021;Hugo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another report showed in preclinical models that combining a BRAF dimer inhibitor with an MEK inhibitor induced a dramatic therapeutic effect and overcame acquired resistance among cancers with KRAS, NRAS, NF1, BRAF non-V600E, and BRAF V600E mutations. Such therapies isolate MEK in RAF complexes, then reduce MEK/MEK dimerization, and uncouple MEK from ERK in acquired resistant tumor subpopulations [ 76 ] ( Table 2 ).…”
Section: Targeting Brafmentioning
confidence: 99%